Engineering Host Microbiome for Crop Improvement and Sustainable Agriculture - Kaul, Sanjana; Choudhary, Malvi; Gupta, Suruchi; Dhar, Manoj K. (Frontiers in Microbiology, 2021)
Dynamic consortium of microbial communities inhabiting inter and intracellular host habitats by colonizing multiple tissue types is designated as plant microbiome. Such an incredible diversity of beneficial microbes renders many ‘ecosystem services’ by emulating symbiotic interactions between plants, soil and microbes for enhanced productivity and sustainability. The interplay between plant and its microbial mutualists supports several agronomic functions, establishing its crucial role in plant beneficial activities. However, functional and mechanistic understanding of plant-microbial ecosystems is still lacking. Therefore, microbiome engineering or host-mediated microbiome engineering represents an emerging biotechnological strategy to directly add, remove or modify community level properties of microbial communities for high specificity and efficacy. The main goal of microbiome engineering is enhancement of plant functions such as combating physiological stresses, as growth promoters, acquisition of essential nutrients, priming host plant defenses, increasing niche breadth, biocontrol agents and in biogeochemical processes. Various ecological, biochemical and molecular approaches have come up as a new paradigm for understanding and manipulating microbiome composition. Further, multidisciplinary approaches and increased ‘omics’ sophistication will provide a predictive framework in achieving a reliable and sustainably engineer plant-microbiome for stress physiology, nutrient recycling and high yielding disease resistant genotypes.